Dinamika Penerimaan Keluarga Terhadap Orang Dengan Skizofrenia Heropnam - Valda Febriyanti Aulia M; Ahmad Ridfah; Andi Nasrawaty Hamid (CV. Ulil Albab Corp, 2023)
In some families, there are many who still think that having a family member with a mental illness is something to be ashamed of. As a result, those who have schizophrenia and are considered to be a shame to the family will be isolated or banished. However, although in some families a family member with schizophrenia might be isolated or banished, there are still families that are willing to take care and accept people with schizophrenia back home. This research aimed to find out the acceptance dynamics of families towards people with schizophrenia heropname and what factors influence the family in accepting or rejecting people with schizophrenia heropname. The methodology used in this research was qualitative method with study case approach. The data collecting technique used in this research was interview conducted to respondents that met the criteria. The responds of this research consisted of two people, namely T and I. The results of this research showed that the two respondents underwent several stages, which were denial, anger, bargaining, depression, and acceptance, and factors that influenced the acceptance towards people with schizophrenia are family’s responses, how the family takes care and nurtures, and expectations. The results of this research can be a source of information related to dynamics of acceptance in the family of people with schizophrenia heropname.